Influence of chronic mercury poisoning upon the connective tissue in rats. II. Effect of mercuric chloride on collagen and elastin - Kucharz, E J; Olczyk, K (Central European journal of public health, 1994)
Rats were intoxicated with mercuric chloride (1 mg/kg b.w.) daily, for 12 weeks. An increase of total collagen and elastin content was found in the skin, the lungs, the liver, the kidneys and the heart muscle. The increase resulted from the elevated level of soluble collagen. These changes were accompanied by elevated hydroxyproline level in serum and urine. It is concluded that chronic intoxication with mercury leads to disturbed composition of the connective tissue matrix.
Keywords: Animals; Rats, Wistar; elastin; Tissue Distribution; Elastin; Collagen; chlorid rtuťnatý; kolagen; otrava rtutí; Male; tkáňová distribuce; krysa rodu Rattus; Mercuric Chloride; chronická nemoc; mužské pohlaví; zvířata; Mercury Poisoning; Chronic Disease; Rats; potkani Wistar